Cost effectiveness of liposomal doxorubicin vs. paclitaxel for the treatment of advanced AIDS–Kaposi's sarcoma. (May 2013) - Raimundo, Karina; Biskupiak, Joseph; Goodman, Michael; Silverstein, Scott; Asche, Carl
Abstract Objective: Epidemic Kaposi's sarcoma (KS) is one of the most common acquired immune deficiency syndrome (AIDS) defining malignancies, a disease with stigmatized clinical features that characterizes the diagnosis of AIDS. This study aims to perform a cost-effectiveness analysis between liposomal doxorubicin and paclitaxel in treating AIDS-KS. Methods: A 21 week decision tree analysis was created using a hospital perspective to compare treatment patterns with liposomal doxorubicin and paclitaxel. All costs were calculated in 2011 US dollars and obtained from an academic treatment center. Acquisition costs were obtained from public estimates using wholesale acquisition cost (WAC). Effectiveness was estimated based on a Phase 3 study of liposomal doxorubicin and paclitaxel (Von-Roenn et al.). Adverse events (AEs) associated with treatment and not the disease were included in the analysis. One-way sensitivity analysis was performed to test the robustness of the results. Results: Cost minimization analysis showed that treatment with liposomal doxorubicin was $18, 125 whereas paclitaxel costs $12, 347. After accounting for response rate, the results showed that liposomal doxorubicin costs $39, 403 versus $21, 661 for paclitaxel. This study has some limitations. Clinical data were derived from different clinical trials. In addition, many assumptions were made. Conclusion: Paclitaxel is dominant due to its lower acquisition cost and high response rate. Acquisition cost of liposomal doxorubicin and paclitaxel are significantly different. After accounting for all the factors that contribute to cost and response rate, paclitaxel is more cost effective than liposomal doxorubicin.